2020
DOI: 10.3389/fnins.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Orexin-A Microinjected Into Central Nucleus of the Amygdala Modulates Feeding and Gastric Motility in Rats

Abstract: Orexin-A is a circulating neuropeptide and neurotransmitter that regulates food intake and gastric motility. The central nucleus of the amygdala (CeA), which regulates feeding behavior and gastric function, expresses the orexin-1 receptor. The aim of this study was to evaluate the effects of microinjection of exogenous orexin-A into the CeA, on food intake and gastric motility, and to explore the mechanisms of these effects. Normal chow and high fat food (HFF) intake were measured, gastric motility and gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…In the context of obesity caused by increased food intakes and/or decreased physical activities, the development of insulin resistance (IR) is considered to be initiated by inflammation of adipose tissue. 44 45 These adipokines and inflammatory cytokines then activate key pathways related to inflammation, proliferation, autophage and mitosis, and subsequently induce the onset of UFs. 46 47…”
Section: Discussionmentioning
confidence: 99%
“…In the context of obesity caused by increased food intakes and/or decreased physical activities, the development of insulin resistance (IR) is considered to be initiated by inflammation of adipose tissue. 44 45 These adipokines and inflammatory cytokines then activate key pathways related to inflammation, proliferation, autophage and mitosis, and subsequently induce the onset of UFs. 46 47…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies support these findings as Dube et al (1999) report no effect of orexin A in the medial preoptic area and arcuate nucleus (Dube et al 1999). Microinjection of orexin A into extra-hypothalamic sites has also been investigated, with studies finding increased food intake when administered into the nucleus accumbens (Mayannavar et al 2014;Sweet et al 2004;, nucleus incertus (Sabetghadam et al 2018) and basomedial amygdala (Wang et al 2018), but not the central amygdala, ventral tegmental area (Dube et al 1999;Jin et al 2020;Sweet et al 1999) and nucleus of the solitary tract (Dube et al 1999;Zheng et al 2005). However, pre-treatment with orexin A injected into the nucleus of the solitary tract significantly induces food intake following intake suppression by intraperitoneal (i.p.)…”
Section: Central Orexin Promotes Feedingmentioning
confidence: 99%
“…For example administration of SB-334867, a selective OXR-1 antagonist, reduces food intake in fasted, food restricted, glucose-deprived or sated animals, both when injected peripherally (Feillet et al 2017;Haynes et al ,2000Haynes et al , , 2002Ishii et al 2004Ishii et al , 2005aIshii et al , 2005bOtlivanchik et al 2015;Rodgers et al 2001;Rorabaugh et al 2014;Valdivia et al 2014;White et al 2005) or centrally into the ventricle (Hsu et al 2015;Karasawa et al 2014;Williams et al 2020;. Other studies investigating the effects of OXR-1 antagonists in specific brain areas found that administration of SB-334867 into the nucleus accumbens (Mayannavar et al 2014;, nucleus of the solitary tract (Kay et al 2014;Williams et al 2020), hypothalamic paraventricular nucleus (Wang et al 2018), but not central amygdala (Jin et al 2020), caused a significant reduction in food intake in rats. Conversely, studies investigating the role of OXR-2 in feeding are rare, with one study finding no effect on food intake after peripheral i.p.…”
Section: Central Orexin Promotes Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effect of UAG on glycolipid metabolism still needs to be further explored. Orexins (hypocretins) are important feeding-related neuropeptides that express in hypothalamic neurons and have an important role in regulating homeostatic systems, including feeding/drinking behaviors, energy homeostasis, energy balance, endocrine functions, and drug addiction [13][14][15][16]. Orexin has two peptide forms, orexin-A (OX-A/hcrt-1) and orexin-B (OX-B/hcrt-2) [17], both of which are from the same peptide, prepro-orexin precursor [18], which is the endogenous ligand for orexin-R1/2 (HcrtR1/2).…”
mentioning
confidence: 99%